Analysis of Customer Relationship Management Implementation at PT. SDI Motor Gresik - Muhammad Fikri Fahrudin; Moh. Agung Surianto (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
PT. Srikandi Diamond Indah Motors Gresik is a Mitsubishi dealer that provides 3S services, namely Sales, Service and Spare parts by serving the sale of Mitsubishi brand passenger vehicles. This study aims to determine the analysis of Customer Relationship Management at PT. Srikandi Diamond Indah Motors Gresik. This study uses a qualitative method. This research approach uses a case study type to reveal carefully, in detail and in depth regarding the implementation of Customer Relationship Management (CRM) at PT. Srikandi Indah Diamond Motors Gresik in establishing relationships with customers. The Analysis Unit includes customers and relevant informants, namely 2 Customers, 1 Marketing Manager and 1 employee. PT. Srikandi Diamond Indah Motors Gresik in implementing Customer Relationship Management by doing. Customer recognition by establishing open and interactive communication with customers can help to understand their needs and preferences more deeply. This can be done by asking relevant questions or offering additional assistance. In conducting customer segmentation, the company does this by grouping them by demographics, geography, needs and benefits. Building interaction with customers, the company does this through customer service, namely customer service, interaction through social media, and also following up customers after the purchase stage is done and not forgetting to conduct customer satisfaction surveys. Adjusting customer needs, the company does this by implementing it by interacting with customers at dealers, company staff interact directly with customers. They provide information about products, help customers choose the right product, and provide the advice they need.